Effect of Irradiation (SRFE) on MSM Photodetectors Device - Srithanachai, Itsara; Sangwaranatee, Narong (My University, 2022)
This paper presents the effect of high energy irradiation expose on metal-semiconductor-metal (MSM) photodetectors device. High energy radiation may impact to lattice structure of semiconductor device. The most impact of radiation on MSM device had been studied base on polycrystalline silicon. Based on our research in SRFE process exposed on P-N power device, radiation will interact with device mechanism and structure that change electrical properties of device. However, MSM device show electrical properties change after irradiation exposure process by photocurrent increased around 4 times when compare with non-irradiated.